EPIGRAPHIC AND PROSOPOGRAPHICAL NOTES ON Q, MARCIUS QUADRATUS FROM IBIDA - Lucrețiu Mihailesu-Bîrliba (Journal of Ancient History and Archaeology)
The author discuss the origin of Q. Marcius Quadratus, whose epitaph was found in Ibida (Moesia inferior). The debate was about a Libyan or a Liburnian origin of Quadratus. Taking into account the occurrences of Marcii in both Dalmatia and Africa, as well the historical content, the author proves that the restitution Libycus is more plausible, identifying the person with a veteran.